Microsoft bookshelf 98 reference library - Microsoft Corporation ([Redmond, Wash.] : Microsoft, 1997)
Contains electronic versions of standard reference sources.
System requirements: Multimedia PC with a 486SX/33MHz or higher processor; Windows 95 or Windows NT version 4.0 ; 8MB RAM fro Windows 95, 12 MB for Windows NT ; at least 10MB hard disk space; 2X CD-ROM drive ; Super-VGA, 256-color monitor ; mouse ; audio board and headphones or speakers ; modem required for Internet links.
Keywords: Interactive multimedia; Electronic encyclopaedia; Reference books -- Software; Encyclopedias and dictionaries -- Software; CD-ROMs.